2015
DOI: 10.1016/j.gaitpost.2015.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic cost of lateral stabilization during walking in people with incomplete spinal cord injury

Abstract: People with incomplete spinal cord injury (iSCI) expend considerable energy to walk, which can lead to rapid fatigue and limit community ambulation. Selecting locomotor patterns that enhance lateral stability may contribute to this population’s elevated cost of transport. The goal of the current study was to quantify the metabolic energy demands of maintaining lateral stability during gait in people with iSCI. To quantify this metabolic cost, we observed ten individuals with iSCI walking with and without exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 29 publications
(42 reference statements)
3
25
0
Order By: Relevance
“…MoS tended to increase with BWS in the Speed-Matched condition, however this increase was not significant and may have been due to our small sample size (n = 8). In addition, step length only reduced when walking speed was decreased in the Dynamically Similar condition, but not in the Speed-Matched condition, which is consistent with other external lateral stabilization studies (Ijmker et al, 2013; Matsubara et al, 2015), but is inconsistent with previous BWS work (Threlkeld et al, 2003). …”
Section: Discussionsupporting
confidence: 55%
“…MoS tended to increase with BWS in the Speed-Matched condition, however this increase was not significant and may have been due to our small sample size (n = 8). In addition, step length only reduced when walking speed was decreased in the Dynamically Similar condition, but not in the Speed-Matched condition, which is consistent with other external lateral stabilization studies (Ijmker et al, 2013; Matsubara et al, 2015), but is inconsistent with previous BWS work (Threlkeld et al, 2003). …”
Section: Discussionsupporting
confidence: 55%
“…Consistent with previous studies [10, 11, 13, 4], our results confirmed that external lateral stabilization provided medio-lateral gait stability, represented by a direct reduction of medio-lateral pelvis displacement which was accompanied by an indirect reduction of step width in stabilized condition. Consistent with Matsubara et al [22], our results confirmed that external lateral stabilization did not constrain the amplitude of anterior-posterior pelvis displacement because bilateral springs were connected to the horizontal trolley which were capable to move freely and in-phase with the displacement of the center of mass in anterior-posterior direction. However, springs fixed in anterior-posterior direction used by previous studies [23, 10, 11, 14] may provide unwanted forces and assistance in the anterior-posterior direction (see Supplementary Material; Figure.…”
Section: Discussionsupporting
confidence: 91%
“…During straight-ahead walking, to compensate for sensory and motor deficits that are known to impair balance [ 39 , 40 ], individuals with neurologic injury often depend heavily on general, passive mechanisms to provide locomotor stability (e.g. decreasing walking speed [ 41 , 42 ], increasing step width [ 14 , 43 45 ], and increasing double support time [ 46 , 47 ]). Older adults [ 48 , 49 ] and individuals with neurologic injury [ 50 , 51 ] may also select compensatory stepping patterns during maneuvers to enhance their passive stability (e.g.…”
Section: Discussionmentioning
confidence: 99%